Pengaruh Profitabilitas, Ukuran Perusahaan Terhadap Struktur Modal Perusahaan Pada Perusahaan Industri Barang Konsumsi Sub Sektor Makanaan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2023 - Neneng Aulia Putri (CV. ITTC INDONESIA, 2025)
This research aims to determine the effect of profitability and company size on the capital structure of the food and beverage subsector during the 2019- 2023 period. Financial data for companies listed on the Indonesia Stock Exchange (BEI) operating in the food and beverage subsector were collected and analyzed using a multiple linear regression approach. The practical implication of this research is that financial managers can consider the level of profitability and company size when designing capital structure policies to maximize company value and optimize financial costs. Apart from that, in 2019 there was a long Covid-19 pandemic and several companies experienced a downturn which had an impact on employees being laid off/laid off.